2015
DOI: 10.1016/j.ebiom.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Brown Fat Stimulation and Insulin Sensitization by a Humanized Bispecific Antibody Agonist for Fibroblast Growth Factor Receptor 1/βKlotho Complex

Abstract: Dissipating excess calories as heat through therapeutic stimulation of brown adipose tissues (BAT) has been proposed as a potential treatment for obesity-linked disorders. Here, we describe the generation of a humanized effector-less bispecific antibody that activates fibroblast growth factor receptor (FGFR) 1/βKlotho complex, a common receptor for FGF21 and FGF19. Using this molecule, we show that antibody-mediated activation of FGFR1/βKlotho complex in mice induces sustained energy expenditure in BAT, browni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
130
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 58 publications
6
130
0
Order By: Relevance
“…These findings are consistent with the relative absence of FGFR1c receptors in adult mouse liver, despite abundantly expressed bKlotho coreceptor (Fon Tacer et al, 2010). Furthermore, an FGFR1c-bKlotho bispecific agonistic antibody was able to activate adipose tissue ERK1/2 but not in liver (Kolumam et al, 2015). Thus, it is considered that several effects of FGF21 on glucose homeostasis, insulin sensitivity, and hepatic steatosis may occur indirectly through stimulation of adiponectin secretion in adipocytes (Lin et al, 2013) or by actions initiated in the central nervous system (Bookout et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These findings are consistent with the relative absence of FGFR1c receptors in adult mouse liver, despite abundantly expressed bKlotho coreceptor (Fon Tacer et al, 2010). Furthermore, an FGFR1c-bKlotho bispecific agonistic antibody was able to activate adipose tissue ERK1/2 but not in liver (Kolumam et al, 2015). Thus, it is considered that several effects of FGF21 on glucose homeostasis, insulin sensitivity, and hepatic steatosis may occur indirectly through stimulation of adiponectin secretion in adipocytes (Lin et al, 2013) or by actions initiated in the central nervous system (Bookout et al, 2013).…”
Section: Discussionsupporting
confidence: 75%
“…Thus, it is considered that several effects of FGF21 on glucose homeostasis, insulin sensitivity, and hepatic steatosis may occur indirectly through stimulation of adiponectin secretion in adipocytes (Lin et al, 2013) or by actions initiated in the central nervous system (Bookout et al, 2013). However, other studies demonstrated rapid hepatic ERK1/2 phosphorylation in mice after pharmacological administration of FGF21 and in isolated hepatocytes treated with FGF21, suggesting direct effects on the liver (Fisher et al, 2011;Jiang et al, 2014;Kolumam et al, 2015). Indeed, we observed enhanced ERK1/2 phosphorylation in mouse livers overexpressing FGF21 (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…This activity was attributed to an increase in Glut1 mRNA and protein expression [14]. In addition, FGF21 and FGF21RA induce expression of Uncoupling protein 1 (Ucp1) mRNA in cultured primary adipocytes [27], [35], [36], [37], which may play a role in inducing white adipose tissue "browning" in mice [27], [38]. At the target tissues, receptor activation by FGF21 triggers a transcriptional response of various genes, including Ucp1 upregulation in adipose tissues [15], [16].…”
Section: The Activity Signature Of Fgf21-class Molecules Cellular Actmentioning
confidence: 99%
“…The rat L6 cell system provides a lower degree of luciferase induction as compared with HEK293 but is more suitable for measuring receptor specificity due to the lack of endogenous FGFR expression [34]. These reporter assays as well as a direct measurement of ERK phosphorylation have been widely used to test and screen various FGF21RAs as well as FGFR4-sparing FGF19 analogs [27], [33], [34], [41], [45].…”
Section: The Activity Signature Of Fgf21-class Molecules Cellular Actmentioning
confidence: 99%
See 1 more Smart Citation